Effect of naphthalene acetic acid on adventitious root development and associated physiological changes in stem cutting of Hemarthria compressa. - Yan-Hong Yan (PLoS ONE, 2014)
In order to find a way to induce rooting on cuttings of Hemarthria compressa cv. Ya'an under controlled conditions, a project was carried out to study the effect of naphthalene acetic acid (NAA) on rooting in stem cuttings and related physiological changes during the rooting process of Hemarthria compressa. The cuttings were treated with five concentrations of NAA (0, 100, 200 300, 400 mg/l) at three soaking durations (10, 20, 30 minutes), and cuttings without treatment were considered as control. Samples were planted immediately into pots after treatment. IAA-oxidase (IAAO) activity, peroxidase (POD) activity and polyphenol oxidase (PPO) activity were determined after planting. Results showed that NAA had positive effect on rooting at the concentration of 200 mg/l compared to other concentrations at 30 days after planting (DAP). Among the three soaking durations, 20 minutes (min) of 200 mg/l NAA resulted in higher percentages of rooting, larger numbers of adventitious roots and heavier root dry weight per cutting. The lowest IAAO activity was obtained when soaked at 200 mg/l NAA for 20 min soaking duration. This was consistent with the best rooting ability, indicating that the lower IAAO activity, the higher POD activity and PPO activity could be used as an indicator of better rooting ability for whip grass cuttings and might serve as a good marker for rooting ability in cuttings.